2023
DOI: 10.1038/s41598-023-37951-y
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in type 2 diabetes comorbidities in different population subgroups: trend analyses using German health insurance data

Abstract: While socioeconomic inequalities in the prevalence and management of type 2 diabetes (T2D) are well established, little is known about whether inequalities exist in the prevalence and the temporal development of T2D comorbidities. Previous research points towards expansion of morbidity in T2D as depicted mainly by a rising trend of T2D comorbidities. Against this background, and using German claims data, this study aims to examine whether socioeconomic status (SES) inequalities exist in the rates and the tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…This hypothesis is also in line with recent increasing trends in type 2 diabetes [ 43 ]. For example, recent evidence points towards a significant increase in type 2 diabetes complications and comorbidities in working-age individuals [ 44 , 45 ]. However, again, more research is needed to formally study the reasons for the observed changes in health over time [ 28 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is also in line with recent increasing trends in type 2 diabetes [ 43 ]. For example, recent evidence points towards a significant increase in type 2 diabetes complications and comorbidities in working-age individuals [ 44 , 45 ]. However, again, more research is needed to formally study the reasons for the observed changes in health over time [ 28 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%